Exosomes Derived From Hypoxia-Conditioned Stem Cells of Human Deciduous Exfoliated Teeth Enhance Angiogenesis via the Transfer of let-7f-5p and miR-210-3p - Liu, Panpan; Qin, Lihong; Liu, Chang; Mi, Jun; Zhang, Qun; Wang, Shuangshuang; Zhuang, Dexuan; Xu, Qiuping; Chen, Wenqian; Guo, Jing; Wu, Xunwei (Frontiers in Cell and Developmental Biology, 2022)
Physiological root resorption of deciduous teeth is a normal phenomenon. How the angiogenesis process is regulated to provide adequate levels of oxygen and nutrients in hypoxic conditions when the dental pulp tissue is reduced at the stage of root resorption is not fully understood. In this study, we designed hypoxic preconditioning (2%) to mimic the physiological conditions. We isolated exosomes from hypoxic-preconditioned SHED (Hypo-exos) cells and from normally cultured SHED cells (Norm-exos). We found that treatment with Hypo-exos significantly enhanced the growth, migration and tube formation of endothelial cells in vitro compared with Norm-exos. We also performed matrigel plug assays in vivo and higher expression of VEGF and higher number of lumenal structures that stained positive for CD31 were found in the Hypo-exos treated group. To understand the potential molecular mechanism responsible for the positive effects of Hypo-exos, we performed exosomal miRNA sequencing and validated that Hypo-exos transferred both let-7f-5p and miR-210-3p to promote the tube formation of endothelial cells. Further study revealed that those two miRNAs regulate angiogenesis via the let-7f-5p/AGO1/VEGF and/or miR-210-3p/ephrinA3 signal pathways. Finally, we found that the increased release of exosomes regulated by hypoxia treatment may be related to Rab27a. Taking these data together, the present study demonstrates that exosomes derived from hypoxic-preconditioned SHED cells promote angiogenesis by transferring let-7f-5p and miR-210-3p, which suggests that they can potentially be developed as a novel therapeutic approach for pro-angiogenic therapy in tissue regeneration engineering.